An analytical study of the results of the TIMSS test for students in the Kingdom of Saudi Arabia and to know the extent to which the mathematics and science curriculum include international test standards - Alsulami, Shrooq Abdulrahim; Alasri, Lama Abdullah; Alamri, Atheer Hassan (Journal of Curriculum and Teaching Methodology, 2022)
The aim of the research is to analyze the results of the TIMSS test for students of the Kingdom of Saudi Arabia and to study the factors affecting their performance. The rapid review of evidence approach was used, by analyzing the results of the TIMSS tests for students in the Kingdom of Saudi Arabia for the fourth primary and second intermediate grades in 2011, 2011 and 2019, and compiling studies analyzing the mathematics and science curricula in light the TIMSS international test standards, as well as studying factors affecting the performance of students in the Kingdom of Saudi Arabia. The results showed that the level of performance of students in the Kingdom of Saudi Arabia in the TIMSS test is low and weak compared to the average performance in the international test, and that there is a disparity and weakness in the curricula’s inclusion of the requirements of the TIMSS tests, and several factors affecting the achievement in this test, the most important of which are the number of teaching hours and the availability of test subjects In curricula and clarity of explanation, in addition to the use of practical experiments in science. Finally, the study recommended several proposals to solve the problem, most notably: Employing the results of studies analyzing mathematics and science curricula in light TIMSS international standards to develop book editions and teacher preparation programs before and during service and recommends the formation of a special committee to evaluate and analyze curricula periodically in line with international standards objectively.